2014
DOI: 10.26740/jaj.v5n2.p115-132
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Good Corporate Governance (Gcg) Dan Corporate Social Responsibility (Csr) Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variable Intervening Pada Perusahaan Pertambangan Yang Go Public Di Bei

Abstract: Application of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) being demands for companles that have involved external parties in fullfilment of the operational funding and have social impact. The effective GCG and CSR will be able to increase the finance performance and value of the firms.This study aimed to determine the direct and indirect effect of GCG dan CSR against the value of the mining companies that go public in BEI, based on sample annual reports 2012. The result of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
1
12
0
5
Order By: Relevance
“…Therefore, financial performance is one of the factors that influence firm value. Ratih & Setyarini (2014), also found that financial performance has a positive effect on firm value. Different results obtained by Anggitasari & Siti (2012), found that financial performance as proxied by ROA does not have a significant effect on firm value.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, financial performance is one of the factors that influence firm value. Ratih & Setyarini (2014), also found that financial performance has a positive effect on firm value. Different results obtained by Anggitasari & Siti (2012), found that financial performance as proxied by ROA does not have a significant effect on firm value.…”
Section: Introductionmentioning
confidence: 89%
“…Teori yang dikemukakan oleh Modigliani dan Miller menjelaskan bahwa nilai perusahaan dapat ditentukan oleh earnings power dari aset perusahaan. Nilai perusahaan (Market Value of The firm) terdiri dari nilai hutang dan nilai saham dibanding nilai asset (dalam (Ratih & Setyarini, 2014). Nilai perusahaan menurut Brigham & Houston (2013), manajemen menggunakan berbagai kebijakan untuk dapat memaksimalkan nilai0perusahaan melalui peningkatan kemakmuran pemilik dan pemegang saham yang dapat dilihat dalam harga saham.…”
Section: Nilai Perusahaanunclassified
“…The influence of GCG on the value of the company directly occurs through investors' reaction by looking at the GCG mechanism applied by the company that makes a positive impact for both internal and external parties, attracting investors who view the company as having good prospects in the future which then affect the increase of company value [14].…”
Section: Indonesiamentioning
confidence: 99%